Does motivation and switching intention affect the trader's decision to choose Baitul Maal wa Tamwil as the intervening variable? - Al-Amin; Asyari (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
For traders and business actors who are motivated and interested in transitioning from conventional to sharia, the existence of Islamic microfinance institutions like Baitul Maal wa Tamwil (BMT) Sidogiri is a blessing. However, it's not solely a blessing; other factors like push-pull mooring (PPM) also play a role, demonstrating the confidence and motivation of business actors in BMT. The purpose of this study is to analyze the effect of push-pull mooring (PPM) mediating, motivation, and switching intention on traders' decisions to choose BMT. The variables in this study include independent variables, namely motivation (X1), and intentiswitching(X2), and the trader's decision to choose BMT (Y), whereas the mediation variable is push-pull mooring (Z). We conducted this research on MSME traders in Mempawah District, West Kalimantan Province, and monitored their decision to choose BMT from September 2023 until its completion. The primary data for this study was collected through questionnaires distributed to MSME traders in Mempawah Regency, West Kalimantan Province. We used the Warp Partial Least Square program for data collection in this study. PLS is a causal modeling approach whose goal is to maximize variable variability. The results of this study are The study concludes that motivation significantly and positively influences push-pull mooring, switching significantly and positively influences the trader's decision to choose BMT, and switching intention significantly and positively influences the trader's decision to choose BMT. Push Pull Mooring Mediates the Influence of Motivation on the Trader's Decision to Choose BMT. Push Pull Mooring Mediates the Effect of Switching Intention on the Trader's Decision to Choose BMT.